Computed tomography findings of periostitis ossificans - Luciana Soares de Andrade Freitas Oliveira; Thaís Feitosa L. de Oliveira; Daniela Pita de Melo; Alynne Vieira de Menezes; Ieda Crusoé Rebello; Paulo Sérgio Flores Campos (Universidade Estadual de Campinas, 2015)
Periostitis ossificans (PO) is a type of chronic osteomyelitis, an inflammation of cortical and cancellous bone. In the maxillofacial region, the mandible is most frequently affected. The cause of inflammatory subperiosteal bone production in PO is spread of infection from a bacterial focus (e.g.: odontogenic disease, pulpal or periodontal infection, and extraction wounds). This pathology is most common in younger people (mean age of 13 years). Conventional radiographs are one of the most useful tools for diagnosis, but in some cases computed tomography (CT) has a key role in both diagnosis and identification of the tissues involved. This paper reports two cases of PO in which CT helped establishing the suspicious etiology: a 12-year-old boy with PO of pulpal origin and a 14-year-old boy with PO of periodontal origin.